Optimization of Product Distribution Cost Furniture UD.SJ using Stepping Stone Method - Fadli Arsi; Dedri Syafei; Silviyani Silviyani (Journal of Engineering Science and Technology Management, 2022)
UD. SJ is one of the SMEs in Pelalawan with the main product in the form of furniture. Problems that are often faced by UD. SJ is the distribution and distribution of costs for product sales that are not optimal, lack of calculations, lack of recording and bookkeeping, thus making UD. SJ sometimes takes a loss. So the formulation in this study is how to optimize the distribution costs of UD products. SJ, the distribution process is influenced by the distance traveled, the cost of the trip, and the number of vehicles and drivers. The purpose of the study was to determine the optimal cost comparison of product distribution in UD. SJ. The method used is the stepping stone transport method). The results showed that the calculation of the distribution costs of furniture products from UD. The optimal SJ using the stepping stone method manually is Rp. 31,233,751.